Evaluación de dos temperaturas en el ciclo biológico de (bactericera cockerelli) en tomate de árbol (solanum betacea), Salache- Cotopaxi 2022. - Gutiérrez Montatixe, Edgar Alexis (2022)
The research was carried out at the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with geographic coordinates of 00º 59' 57'' South latitude and 78º 37' 14'' West longitude. With the objective of evaluating the biological development of (Bactericera cockerelli.) at two temperatures (10 – 15 °C). The methodology applied was Quantitative, and the Observation Technique was mainly used. It consisted of observing the development of (Bactericera cockerelli.) at two controlled temperatures in growth chambers, developed at the university, with fresh tree tomato leaves as a host. The samples were randomly collected from the crops that presented insects of (Bactericera cockerelli.) found in the foliar part of the crop, geographically referenced (GPS points, temperature, altitude, humidity). Afterwards, the samples were transported to the entomology laboratory for their respective rearing in the growth chambers with controlled temperature and feeding conditions for the development of the insects. Therefore, the research had a daily evaluation based on data collection, observation of each stage, and always aware of the insect feeding and temperature review, which remained constant at 10°C and 15°C. As a result, two life tables were obtained at 10 °C and 15 °C, to obtain results and discuss about the processes of life cycle, sex and oviposition of the insect, which grant to design a model of each biological stage of insects. From the results it can be said biologically that the development of the insect took 5 days for the two temperatures of 10°C and 15°C.